Key buildings from prehistory to the present : plans, sections and elevations - Ballantyne, Andrew (London : Laurence King Publishing, 2012)
Features around 150 of the most significant buildings in the history of world architecture, from the pyramids and the Parthenon to some of the most important works by recent architects. The buildings are organized by type - from places of worship and public buildings to houses-and are divided into nine chapters, each with an informative introduction that surveys the history of that type. For each building there are numerous, accurate scale drawings showing a combination of floor plans, elevations and sections as appropriate, all specially redrawn for this book.
Culture-defining monuments -- Dwellings -- Places of worship -- Bridges and defenses -- Production, trade and education -- Government administration -- Culture and entertainment -- Memorials -- Public spaces.
Includes bibliographical references and index.
Keywords: ARCHITECTURE -- HISTORY; ARCHITECTURAL DESIGN; ARCHITECTURE -- DESIGNS AND PLANS